Automated ribotyping to distinguish the different non Sau/ non Sep staphylococcal emerging pathogens in orthopedic implant infections - Campoccia, D; Baldassarri, L; An, Y H; Kang, Q K; Pirini, V; Gamberini, S; Pegreffi, F; Montanaro, L; Arciola, C R (International journal of artificial organs, 2006)
Several species belonging to Staphylococcus genus, other than Staphylococcus aureus and Staphylococcus epidermidis (non Sau/ non Sep species), exhibit increasing abilities as opportunistic pathogens in the colonisation of periprosthetic tissues. Consequently, the availability of means for accurate identification is crucial to assess the pathogenic characteristics and to clarify clinical relevance of the individual species. Here, 146 clinical staphylococcal isolates belonging to non Sau/ non Sep species from prosthesis-associated orthopedic infections were analyzed by conventional enzymatic galleries and by automated ribotyping. Twelve different species were recognised: S. capitis, S. caprae, S. cohnii, S. equorum, S. haemolyticus, S. hominis, S. lugdunensis, S. pasteuri, S. sciuri, S. simulans, S. warneri, S. xylosus. Ribotype identifications were compared with the phenotypes obtained by the Api 20 Staph system and/or ID 32 Staph system. ID 32 Staph profiles were more consistent with ribotyping results than Api Staph profiles. Across the different staphylococcal species investigated, correct identifications with Api Staph were 45%, while with ID 32 Staph they were 59%. It has, however, to be mentioned that ID 32 Staph was mostly applied to discriminate unmatched ribotyping and Api Staph identifications, thus to a subpopulation of strains with ""atypical"" metabolic profile. Automated ribotyping provided a correct identification for 91% of the isolates. These results confirm automated ribotyping as a convenient rapid technique, still subject to improvements, which will accurately and rapidly recognise the newly emerging staphylococcal pathogens in implant-related orthopedic infections.